2014
DOI: 10.1364/oe.22.001127
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of aerosol phase function and vertical backscattering coefficient using a charge-coupled device side-scatter lidar

Abstract: In theory, lidar overlap factor can be derived from the difference between the particle backscatter coefficient retrieved from lidar elastic signal without overlap correction and the actual particle backscatter coefficient, which can be obtained by other measured techniques. The side-scatter signal using a CCD camera is testified to be a powerful tool to detect the particle backscatter coefficient in near ground layer during night time. In experiment, by combining side-scatter and back-scatter signals the geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…When the aerosol backscatter coefficient value at the scattering angle θ c as the reference point is known, according to Eq. (1), the backscattering or extinction coefficient of aerosol can be derived in our proposed numerical inversion method (Tao et al, 2014b). The validation experiments and error analysis are shown in the reference (Tao et al, 2015).…”
Section: Retrieved Methods Of Aerosol Extinction Profilementioning
confidence: 99%
“…When the aerosol backscatter coefficient value at the scattering angle θ c as the reference point is known, according to Eq. (1), the backscattering or extinction coefficient of aerosol can be derived in our proposed numerical inversion method (Tao et al, 2014b). The validation experiments and error analysis are shown in the reference (Tao et al, 2015).…”
Section: Retrieved Methods Of Aerosol Extinction Profilementioning
confidence: 99%
“…For this CCD lidar equation, there are three different aspects compared to the backscattering lidar: (I) received signals without range square dependence, (II) no overlap factor, and (III) variable vertical altitude resolution, and the closer to the surface, the better the resolution. By solving this overlap problem, the side‐scattering lidar is suitable especially for detecting the aerosol vertical profile in the near range, and it can provide a fine vertical resolution due to the elaborate optics design (Tao et al, ; Wang et al,).…”
Section: Instruments and Methodsmentioning
confidence: 99%
“…Their results demonstrated that the CCD laser detection system is reliable in monitoring vertical structures of aerosol optical properties. For example, the aerosol extinction coefficient and the aerosol phase function can be derived with the CCD lidars (Bian, Zhao, Xu, Ma, et al, ; Bian, Zhao, Xu, Tao, et al, ; Tao et al, ). Nevertheless, in one side its advantage is applied to the remote sensing of the nocturnal aerosol layers but not for daytime.…”
Section: Introductionmentioning
confidence: 99%
“…Particle backscatter coefficient can be retrieved from elastic signal using Fernald method [8]. The backscattering coefficient can also be retrieved from side-scatter technique by numerical inversion method [9]. An iterative algorithm is developed to determine GFF from lidar elastic signal in 532 nm when the profile of particle backscatter coefficient had been known correctly.…”
Section: Methodsmentioning
confidence: 99%